EXAMINATION OF ADAPTIVE AND AGRONOMIC CHARACTERS IN LINES OF COMMON WHEAT OMSKAYA 37 BEARING TRANSLOCATIONS 1RS.1BL AND 7DL-7Ai - I. A. Belan; L. P. Rosseeva; V. M. Rosseev; E. D. Badaeva; Y. I. Zelenskiy; N. P. Blokhina; S. S. Shepelev; L. A. Pershina (Вавиловский журнал генетики и селекции)
Lines derived from spring bread wheat Omskaya 37 and possessing wheat-rye translocation 1RS.1BL have been studied and tested for resistance to fungal pathogens, drought, crop yield, and parameters characterizing ecological plasticity and stability. Three lines have been studied with the use of the C-banding technique. It is shown that these lines, in addition to wheat-rye translocation 1RS.1BL possess wheat-wheatgrass translocation 7DL-7Ai, where a segment of chromosome 7Ai of Agropyron elongatum (= Thinopyrum elongatum ; = Thinopyrum ponticum) is translocated to the long arm of wheat chromosome 7D. It is concluded that the complex stability of Omskaya 37 and its promising lines is related to the influence of a cluster of genes located on segments of rye and Agropyron chromosomes involved in the respective wheat–alien translocations. Several promising lines are recommended for further use in breeding programs. One of the lines we consider here, Lutescens 242/97-2-10, is submitted to state variety trial for registration as spring wheat variety Omskaya 41.